Features and processes of rock weathering in central Dronning Maud Land, Antarctica - Elvevold, Synnøve; Engvik, Ane K.; Sunde, Øyvind (Geomorphology, 2024)
In this study, we have investigated rock weathering phenomena in the central part of Dronning Maud Land, Antarctica. The area is characterized by low mean annual temperatures (−18 °C), strong katabatic winds, and minimal liquid water at the surface. Weathering features, including ventifacts, tafoni, and grus accumulations, are characterized through field observations, rock surface temperature measurements, and microscopic analysis. Abrasion by sand and ice particles transported by strong winds has locally resulted in ridge-shaped ventifacts and rock surfaces with elongated pits, furrows, and grooves. The abrasion-caused features, such as polished facets, keels, and grooves, indicate a northeast-facing wind direction, aligning with the present-day wind regime. The dominant weathering processes in coarse-grained intrusive rocks are oxidation and granular disintegration. Fe-oxidation induces cracking, increasing the porosity and enhancing susceptibility to further weathering. Additionally, temperature fluctuations on rock surfaces caused by solar radiation create thermal stress, which can lead to the formation of microcracks. These microcracks, formed due to thermal expansion, are likely to propagate through subcritical cracking, which is a slow, long-term process. Together, Fe-oxidation, thermal expansion, and subcritical cracking are important mechanisms contributing to long-term weathering and rock decay. Salt weathering, facilitated by snow and ice meltwater, particularly within tafoni, leads to flaking and disintegration of the parent rock. These findings shed light on the complex interactions shaping the geomorphology of central Dronning Maud Land and provide insights into long-term weathering processes operating in Antarctica's extreme environment.
Article number: 109435
Keywords: Dronning Maud Land; geologi; geomorfologi

Mineralogical and Geochemical Response to Fluid Infiltration into Cambrian Orthopyroxene-Bearing Granitoids and Gneisses, Dronning Maud Land, Antarctica - Engvik, Ane K.; Corfu, Fernando; Kleinhanns, Ilka C.; Taubald, Heinrich; Elvevold, Synnøve (Minerals, 2024)
Fluid infiltration into Proterozoic and Early Palaeozoic dry, orthopyroxene-bearing granitoids and gneisses in Dronning Maud Land, Antarctica, has caused changes to rock appearance, mineralogy, and rock chemistry. The main mineralogical changes are the replacement of orthopyroxene by hornblende and biotite, ilmenite by titanite, and various changes in feldspar structure and composition. Geochemically, these processes resulted in general gains of Si, mostly of Al, and marginally of K and Na but losses of Fe, Mg, Ti, Ca, and P. The isotopic oxygen composition (δ18OSMOW = 6.0‰–9.9‰) is in accordance with that of the magmatic precursor, both for the host rock and infiltrating fluid. U-Pb isotopes in zircon of the altered and unaltered syenite to quartz-monzonite indicate a primary crystallization age of 520.2 ± 1.0 Ma, while titanite defines alteration at 485.5 ± 1.4 Ma. Two sets of gneiss samples yield a Rb-Sr age of 517 ± 6 Ma and a Sm-Nd age of 536 ± 23 Ma. The initial Sr and Nd isotopic ratios suggest derivation of the gneisses from a relatively juvenile source but with a very strong metasomatic effect that introduced radiogenic Sr into the system. The granitoid data indicate instead a derivation from Mid-Proterozoic crust, probably with additions of mantle components.
Keywords: Dronning Maud Land; NARE 1996/97; geokjemi; geokronologi; geologi; mineralogi

Radar internal reflection horizons from multisystem data reflect ice dynamic and surface accumulation history along the Princess Ragnhild Coast, Dronning Maud Land, East Antarctica - Koch, Inka; Drews, Reinhard; Franke, Steven; Jansen, Daniela; Oraschewski, Falk Marius; Muhle, Leah Sophie; Višnjević, Vjeran; Matsuoka, Kenichi; Pattyn, Frank; Eisen, Olaf (Journal of Glaciology, 2024)
Ice shelves, which regulate ice flow from the Antarctic ice sheet towards the ocean, are shaped by spatiotemporal patterns of surface accumulation, surface/basal melt and ice dynamics. Therefore, an ice dynamic and accumulation history are imprinted in the internal ice stratigraphy, which can be imaged by radar in the form of internal reflection horizons (IRHs). Here, IRHs were derived from radar data combined across radar platforms (airborne and ground-based) in coastal eastern Dronning Maud Land (East Antarctica), comprising three ice rises and adjacent two ice shelves. To facilitate interpretation of dominant spatiotemporal patterns of processes shaping the local IRH geometry, traced IRHs are classified into three different types (laterally continuous, discontinuous or absent/IRH-free). Near-surface laterally continuous IRHs reveal local accumulation patterns, reflecting the mean easterly wind direction, and correlate with surface slopes. Areas of current and past increased ice flow and internal deformation are marked by discontinuous or IRH-free zones, and can inform about paleo ice-stream dynamics. The established IRH datasets extend continent-wide mapping efforts of IRHs to an important and climatically sensitive ice marginal region of Antarctica and are ready for integration into ice-flow models to improve predictions of Antarctic ice drainage.
Edition: 2023/12/12 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; teknologi

Permafrost and ground-ice conditions in the Untersee Oasis, Queen Maud Land, East Antarctica - Lacelle, Denis; Verret, Marjolaine; Faucher, Benoit; Fisher, David; Gaudreau, Adam; Pellerin, André; Ecclestone, Miles; Andersen, Dale T. (Antarctic Science, 2024)
Knowledge of Antarctic permafrost is mainly derived from the Antarctic Peninsula and Victoria Land. This study examines the 2019–2023 temperature and humidity conditions, distribution and development of polygonal terrain and the origin of ground ice in soils of the Untersee Oasis. In this region, the surface offset (MAAT ≅ MAGST) and the thermal offset (MAGST ≤ TTIT) reflect the lack of vegetation, absence of persistent snow and a dry soil above the ice table. The mean annual vapour pressure at the ground surface is approximately ~2× higher than in the air but is ~0.67× lower than at the ice table. The size of polygons appears to be in equilibrium with the ice-table depth, and numerical modelling suggests that the depth of the ice table is in turn in equilibrium with the ground surface temperature and humidity. The ground ice at the ice table probably originates from the partial evaporation of snowmelt that infiltrated the dry soil column. As such, the depth of the ice table in this region is set by the water vapour density gradient between the ground surface and the ice-bearing ground, but it is recharged periodically by evaporating snowmelt.
Edition: 2024/12/17 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; fysisk geografi; geologi; permafrost

Hydrography and circulation below Fimbulisen Ice Shelf, East Antarctica, from 14 years of moored observations - Lauber, Julius; Hattermann, Tore; de Steur, Laura; Darelius, Elin; Fransson, Agneta (Ocean Sci., 2024)
Future mass loss from the East Antarctic Ice Sheet represents a major uncertainty in projections of future sea level rise. Recent studies have highlighted the potential vulnerability of the East Antarctic Ice Sheet to atmospheric and oceanic changes, but long-term observations inside the ice shelf cavities are rare. Here, we present new insights from observations from three oceanic moorings below Fimbulisen Ice Shelf from 2009 to 2023. We examine the characteristics of intrusions of modified Warm Deep Water (mWDW) across a sill connecting the cavity to the open ocean and investigate seasonal variability of the circulation and water masses inside the cavity using an optimum multiparameter analysis. In autumn, the water below the 345 m deep central part of the ice shelf is composed of up to 30 % solar-heated, buoyant Antarctic Surface Water (ASW), separating colder Ice Shelf Water from the ice base and affecting the cavity circulation on seasonal timescales. At depth, the occurrence of mWDW is associated with the advection of cyclonic eddies across the sill into the cavity. These eddies reach up to the ice base. The warm intrusions are observed most often from January to March and from September to November, and traces of mWDW-derived meltwater close to the ice base imply an overturning of these warm intrusions inside the cavity. We suggest that this timing is set by both the offshore thermocline depth and the interactions of the Antarctic Slope Current with the ice shelf topography over the continental slope. Our findings provide a better understanding of the interplay between shallow inflows of ASW contributions and deep inflows of mWDW for basal melting at Fimbulisen Ice Shelf, with implications for the potential vulnerability of the ice shelf to climate change.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; hydrografi; isshelf; klimaendringer; klimatologi; oseanografi

Supraglacial lake evolution and its drivers in Dronning Maud Land, East Antarctica - Mahagaonkar, Anirudha; Moholdt, Geir; Glaude, Quentin; Schuler, Thomas Vikhamar (Journal of Glaciology, 2024)
Supraglacial lakes on Antarctic ice shelves can have far-reaching implications for ice-sheet stability, highlighting the need to understand their dynamics, controls and role in the ice-sheet mass budget. We combine a detailed satellite-based record of seasonal lake evolution in Dronning Maud Land with a high-resolution simulation from the regional climate model Modèle Atmosphérique Régional to identify drivers of lake variability between 2014 and 2021. Correlations between summer lake extents and climate parameters reveal complex relationships that vary both in space and time. Shortwave radiation contributes positively to the energy budget during summer melt seasons, but summers with enhanced longwave radiation are more prone to surface melting and ponding, which is further enhanced by advected heat from summer precipitation. In contrast, previous winter precipitation has a negative effect on summer lake extents, presumably by increasing albedo and pore space, delaying the accumulation of meltwater. Downslope katabatic or föhn winds promote ponding around the grounding zones of some ice shelves. At a larger scale, we find that summers during periods of negative southern annular mode are associated with increased ponding in Dronning Maud Land. The high variability in seasonal lake extents indicates that these ice shelves are highly sensitive to future warming or intensified extreme events.
Edition: 2024/10/02 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; fjernmåling; glasiologi; innlandsis; isshelf; klimamodeller; subglasial innsjø

The Troll Observing Network (TONe): A contribution to improving observations in the data-sparse region of Dronning Maud Land, Antarctica - Pedersen, Christina A.; Njåstad, Birgit; Aas, Wenche; Darelius, Elin; Descamps, Sébastien; Flått, Stig; Hattermann, Tore; Hudson, Stephen R.; Miloch, Wojciech J.; Rykkje, Simen; Schweitzer, Johannes; Storvold, Rune; et al. (Polar Research, 2024)
Understanding how Antarctica is changing and how these changes influence the rest of the Earth is fundamental to the future robustness of human society. Strengthening our understanding of these changes and their implications requires dedicated, sustained and coordinated observations of key Antarctic indicators. The Troll Observing Network (TONe), now under development, is Norway’s contribution to the global need for sustained, coordinated, complementary and societally relevant observations from Antarctica. When fully implemented within the coming three years, TONe will be a state-of-the-art, multi-platform, multi-disciplinary observing network in data-sparse Dronning Maud Land. A critical part of the network is a data management system that will ensure broad, free access to all TONe data to the international research community.
Section: Perspectives
Keywords: Antarktis; Dronning Maud Land; Sørishavet; Troll forskningsstasjon; biologi; datainnsamling; forskningsinfrastruktur; fysikk; geologi; internasjonal samarbeid; kjemi